(untitled) (Health Renaissance, 2017)
Background: Knowledge, attitudes and practices (KAP) surveys are possibly the most frequently used studies in health-seeking behaviour research. Health care workers serve as key players in the prevention and management of diseases. Their perceptions, attitudes and practices have implications for the management of diseases in both health centers and communities. Objective: To assess knowledge, attitude and practice towards STDs among health attendant staffs (health aids and health attendants) of BPKIHS. Methods: This is a descriptive cross sectional study. The study population was Health attendants and Health aids workers working in different departments of BPKIHS. Modified structured questionnaire was used for data collection. SPSS version 11.5 was used for data entry and analysis. Results: 180 Health attendants and Health aids working in different departments of BPKIHS participated in the study. 29% belonged to 30-34 age groups. 86% of study population had heard about STD/HIV/AIDS. 29% expressed that having intercourse without using condoms is known as unprotected sex. Unprotected sexual habits (40.6%), using mask, gloves while working (30%) were methods listed for prevention of transmission of STDs/HIV/AIDS. Conclusion: Majority were from 30-39 years group.86% had heard about STDs/HIV/AIDS. The commonest method to protect from STDs/HIV/AIDS were listed as avoiding multiple sex partners and use gloves and mask while working. Health Renaissance 2015;13 (3): 95-106